2014
DOI: 10.1049/el.2014.2228
|View full text |Cite
|
Sign up to set email alerts
|

AC response of 0.35 µm CMOS triple‐junction photodetector

Abstract: A vertically stacked triple-junction photodiode (PD) is characterised for its suitability for sensor applications which demand a high speed. The proposed PD is implemented in a 0.35 µm CMOS process without process modifications. The AC performance of the detector is characterised at three wavelengths, blue (410 nm), green (520 nm) and red (675 nm). The measurements are carried out with a high dynamic range to fully characterise possible interactions between the different wavelengths (cross-coupling mechanisms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…It is particularly attractive for multispectral applications, such as color detection, light wavelength characterization and simultaneous spectral analysis of several light sources [3,4,6,7,9,11,12,14,[15][16][17]. It has been also shown that this kind of photodetector is well adapted to optical data communication of more than 100 Mbits/s [18][19][20], where the BMJ photodetectors permit the natural demultiplexing of separate incident light sources.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is particularly attractive for multispectral applications, such as color detection, light wavelength characterization and simultaneous spectral analysis of several light sources [3,4,6,7,9,11,12,14,[15][16][17]. It has been also shown that this kind of photodetector is well adapted to optical data communication of more than 100 Mbits/s [18][19][20], where the BMJ photodetectors permit the natural demultiplexing of separate incident light sources.…”
Section: Applicationsmentioning
confidence: 99%
“…In such conditions, the band-to-band tunneling (BBT) is not negligible. Its contribution is formulated from the conventional Zener tunneling equation: (20) where C bbtθ and E 0 are constants that are highly dependent on the device material; the E MAXθ are the maximum electrical fields in each depletion zone.…”
Section: Equivalent Circuitmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of stacked photodiodes for vision sensors has been explored by different authors [6]- [8], [12]. The transient response of these different stacked photodiodes have been analyzed for communications applications; for instance, [13], [14]. Image sensors with stacked diodes are also commercialized by Foveon [11].…”
Section: Enhanced Sensitivity Of Cmos Imagementioning
confidence: 99%